Complex dynamics in fashion life cycles - Bert Hofman; Michael Rauscher (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1991)
Fashions and their revivals occur in a rather erratic manner. The paper shows that such fluctuations can be derived from the utility maximizing behaviour of rational individuals with stable preferences. It is assumed that the demand for the fashion good is determined, amongst other variables, by the social environment the individual is living in. There are positive and negative consumption externalities. If there are lags in the reaction of the individual to what other people do, then the demand for fashion goods may fluctuate over time. For certain parameter constellations, there may even be deterministic chaos.
Keywords: 330; Mode; Konsumtheorie; Externer Effekt; Chaostheorie; Theorie